Prevalence and correlates of severe problematic cannabis use: analysis of a population-based survey in Jamaica - Lalwani, Kunal; De La Haye, Winston; Kerr, Kevon; Abel, Wendel; Sewell, Clayton (Frontiers in Psychiatry, 2024)
BackgroundThere is an increasing demand for the treatment of problematic cannabis use (PCU) in low-income and middle-income countries. Jamaica’s historical inclination towards cannabis use underscores the need for research in addressing this issue.ObjectivesTo determine the prevalence and patterns of cannabis use and assess the sociodemographic factors, psychosocial correlates, knowledge and perceptions associated with severe PCU among Jamaicans using nationally representative data.MethodsThis study involved a secondary data analysis of the last Jamaica National Drug Prevalence Survey. It included 786 participants who used cannabis in the past year and completed the Cannabis Abuse Screening Test (CAST). The CAST has been validated against the Diagnostic and Statistical Manual of Mental Disorders (DSM), with a score ≥ 7 meeting the criteria for severe PCU. CAST scores were dichotomized utilizing these thresholds, and data generated were analyzed with SPSS version 25 using Pearson’s χ2 test and logistic regression.ResultsIn the past year, 53.3% of Jamaicans who smoked cannabis had a score of 7 or higher on the CAST and smoked an average of 62.21 joints per month. Male respondents were twice as likely to have severe PCU as females. Additionally, young, middle, and older adults were respectively 3, 5 and 3 times more likely to report severe PCU compared to adolescent respondents. Participants who started cannabis use at 11 years and under, 12-17 years, and 18-25 years were respectively 5, 7 and 7 times more likely to report severe PCU than those at 26 years and older. Moreover, easy access to cannabis, a high perceived need for treatment, belief in increased national drug use prevalence, and awareness of the National Drug Control and Prevention Agency were associated with increased odds of reporting severe PCU.ConclusionOne out of every two Jamaicans who used cannabis in the past year reported severe PCU and smoked an average of two cannabis joints per day. Early initiation increases the risk of severe PCU. Accordingly, a public health approach involving multiple sectors is needed to provide treatment options.